Efficiency Analysis of Data Compression of Power System Transients using Wavelet Transform - Shang, Li; Jäger, Johann; Krebs, Rainer (2003 IEEE Bologna PowerTech, 2003)
This paper analyzes the wavelet transform application in the data compression of power system transients. It studies the influences on the compression efficiency and quality by different mother wavelets, scale levels and thresholdings. It presents the relation between the compression efficiency and the compression accuracy, and shows how to get the optimal solution. It shows that the wavelet transform leads to a data compression approach with high compression efficiency, high compression accuracy, high compression quality and good denoising effect, so that the wavelet transform can bring remarkable advantages to the fields in which big amounts of data are processed like fault recording and SCADA/EMS/DMS system
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.leen.effici
Keywords: Data compression efficiency; data compression; wavelet; wavelet transform; power system transients; denoising